2009
DOI: 10.1177/1059601109350980
|View full text |Cite
|
Sign up to set email alerts
|

Commitment to Change: Contributions to Trust in the Supervisor and Work Outcomes

Abstract: There is a lack of empirical evidence on the relationship between commitment to change, trust in organizational authorities, and work outcomes. The purpose of this study is to bring further evidence on the role played by affective and continuance commitment to change on employee’s trust in the supervisor and several work outcomes (turnover intentions, organizational citizenship behaviors, and perceived performance). Participants were 221 employees from several organizations that had undergone major organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 64 publications
1
89
0
2
Order By: Relevance
“…Previous literature shows that employees trust in their leadership can lead toward desirable outcomes, such as a higher level of performance (Neves & Caetano, 2009) and greater exchange of ideas and knowledge (Renzl, 2008). In previous literature, trust has been conceptualized in several different ways.…”
Section: Employees' Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature shows that employees trust in their leadership can lead toward desirable outcomes, such as a higher level of performance (Neves & Caetano, 2009) and greater exchange of ideas and knowledge (Renzl, 2008). In previous literature, trust has been conceptualized in several different ways.…”
Section: Employees' Trustmentioning
confidence: 99%
“…Trust leads to greater employee confidence in a leader's fair intentions behind the change (Harvey, Royal, & Stout, 2003). Past research demonstrates that trust in leadership is an important element for organizational change (Smollan, 2013), and might be as a consequence or a predecessor of the relationship at work (Neves & Caetano, 2009;Saunders & Thornhill, 2003).…”
Section: Occ Employees' Trust and Leadershipmentioning
confidence: 99%
“…Beside on social exchange theory, Tan et al (2009) reported trust in organization significantly and fully mediates the relationships between trust in co-worker and affective commitment. Neves et al (2009) found trust in supervisor fully mediates the relationships between affective commitment and employee performance. Hence, the proposed hypothesis is:…”
Section: Performance Appraisalmentioning
confidence: 99%
“…The higher affective commitment is a predictor of the employees' superior performance and strengthens toward employees' trust (Gong et al 2009). While, Neves et al (2009) reported that trust as a full mediation effects on staffing toward performance appraisal and affective commitment. However, the mediation result of the present research is reported that trust partially mediates on the relationship between performance appraisal and affective commitment.…”
Section: Performance Appraisalmentioning
confidence: 99%
See 1 more Smart Citation